Socio-demographic profile and health needs of HIV patients: a study at a tertiary care teaching hospital - Saravade, Amol; Shenoy, Anita; Shinde, Ratnendra; Nile, Rachana (International Journal Of Community Medicine And Public Health, 2017)
Background: AIDS the acquired immune deficiency syndrome is a fatal illness caused by a retrovirus known as the human immune deficiency virus (HIV) which breaks the body’s immune system, leaving the victim vulnerable to a host of life. It is essential to understand the priority needs of PLHIV. So that medical and non-medical, social, cultural and economical interventions can be planned to bring them in the mainstream of the society. Objective was to study the socioeconomic and demographic profile of the HIV positive patients registered at an ART clinic and to enlist and prioritize their health and other needs. Methods: The study was carried out at an ART clinic in a tertiary care centre in Mumbai. Only HIV positive patients registered at ART clinic and willing to participate in study and HIV positive patient above 18 years of age were included in the study while HIV positive patient not willing to participate in study were excluded from the study. The study was carried out during the period of April 2013 to December 2013. The statistical analysis was performed using Microsoft Excel. Results: Total number of respondents was 180. The mean age of study group is 35.49 years. Majority of the respondents had acquired at least primary or secondary education in schools, 18 (10%) respondents were graduates and only 3 (1.67%) with a post graduate degree. The priority needs as perceived by the subjects were classified as immediate, intermediate and long term needs. Conclusions: The study showed that the demographic and socioeconomic profile of the respondents reflects the same trend as at national level. The published data by ‘NACO’ corroborates these findings. A substantial proportion of the total HIV +ve cases reported are living below poverty line (31.6%). This could require special interventions to ensure that they were treated for opportunistic infections and for reducing the viral load.